Evaluation of Environment, Social, and Governance (ESG) Implementation at PT XYZ - Purba, Yohanna Bregiba Lolaninta Br; Wardhani, Ratna (E-Jurnal Akuntansi; Vol 35 No 7 (2025), 2025)
Sustainability issues have encouraged companies to integrate Environmental, Social, and Governance (ESG) principles into their business strategies, including in the banking sector. This study aims to evaluate ESG implementation at PT XYZ from a management perspective that includes perceived benefits, strategies and initiatives, as well as challenges and outlook. The study used a single case study qualitative approach with semi-structured interview techniques to nine informants who have direct responsibility for ESG implementation. Data were analyzed thematically and strengthened by stakeholder and legitimacy theories. The results show that ESG implementation has provided real benefits, especially in social and governance aspects, such as improved reputation, customer loyalty, and transparency. However, the contribution of environmental aspects is still limited and ESG impact measurement is not yet systematic. The main challenges come from internal coordination, limited resources, and regulatory uncertainty. PT XYZ is considered to need to strengthen its ESG organizational structure, improve cross-functional training, and adopt a digital system for sustainability reporting. This study provides practical insights for other financial institutions that are pioneering ESG integration and enriches understanding of ESG as a strategy for legitimacy and stakeholder engagement.  Keywords: Environmental, Social, and Governance (ESG); Management Perspective; Perceived Benefits; Challenges and Obstacles to ESG Implementation